High Organic Wastewater from Fermented Rice Noodles Factories and Slaughterhouses Treated by Anaerobic Filter Tank System Combined with Floating Plants at Different Hydraulic Retention Times - Kanchak, Angsuma; Kengchuwong, Metta; Sanghaw , Ratikorn; Nuasri, Chompoo (Burapha Science Journal, 2026)
The objectives of this research were to study and compare the efficiency of anaerobic filter tank system in combined with floating plants at different hydraulic retention times in treatment of high organic wastewater. The experiments were divided into 2 sets, i.e. the first set, the treatment of wastewater from the Fermented Rice Noodles Factory with anaerobic filter tank system with water lettuce (a floating plant) and the second set, the treatment of wastewater from the slaughterhouse with anaerobic filter tank system with water hyacinth (a floating plant). There was design for continuous wastewater intake of 40 liters per day, using water retention periods 6, 12, 18, 21, 24 and 36 hours. Water samples were taken in and out of the system for analyzing of suspended solids, BOD and COD. The statistics used to analyze the data were mean, standard deviation, and compared the difference in treatment efficacy with F-test (One-way ANOVA) statistic at the .05 level. The study results on the efficiency of the anaerobic filter system with floating plants at the water retention periods of 6, 12, 18, 21, 24 and 36 hours showed that both sets of experiments were able to treat more suspended solids when the water retention period was longer. The treatment efficiency in Fermented Rice Noodles Factories wastewater were 23.31, 16.87, 36.95, 26.04 and 49.14 %, respectively, and slaughterhouse wastewater were 23.99, 34.37%, 41.25, 44.75 and 50.12 %, respectively. Efficiency of treated BOD and COD were found that at the water retention period of 12 hours, wastewater of Fermented Rice Noodles Factories can be treated at a maximum of 23.60 % and 36.12%, and at the water retention period 24 hours, the slaughterhouse wastewater can be treated at a maximum of 52.78% and 39.79 %. When comparing the treatment efficiency of two trials, it was found that efficiency of suspended solids treatment was significantly different, while BOD and COD were not statistically significant difference at .05 level.